Tissue depletion of doxycycline after its oral administration in food producing chicken for fattening - Mestorino, Olga Nora (2018)
Doxycycline (DOX), tetracycline of second generation, is mainly active against Gram–positive and Gram–negative bacteria, aerobic and anaerobic. Although there are few pharmacokinetic studies in chickens, it is frequently used for the colibacillosis treatment, salmonellosis, staphylococcal infections, avian mycoplasmosis and chlamydia. The objective of this study was to evaluate the withdrawal time (WT) of DOX formulation at 25 % in edible tissues, after its oral (PO) use in broilers. Forty healthy chicks (30–35 days of age) were used. DOX was administered with drinking water for 5 days at 10 mg kg–1 (N = 36); four untreated animals were reserved (control). Six animals per group were euthanized by cervical dislocation after desensitization by passage of an electric current through the head, after 24 hours until 9 d post treatment and control animals also. Muscle, liver, kidney and skin/fat samples were obtained. DOX was determined by HPLC with UV detection. DOX concentrations were determined in all tissues examined; generally falling below the MRL at 7 d after administration is terminated. It was estimated 6.58, 8.18, 8.69 and 6.96 d of WT for muscle, liver, kidney and skin/fat, respectively. After DOX administration at a rate of 10 mg kg–1 for 5 days in drinking water, a WT of 9 d is suggested in poultry destined for human consumption.